New findings of Isidella elongata (Esper, 1788) in the Levantine-Balearic demarcation (western Mediterranean Sea) - FARRIOLS, MARIA TERESA; FRANK, AIDA; ORDINES, FRANCESC; CALERO, BELÉN; PAREJO, AÍDA; DE MESA, AINA; COHEN-SÁNCHEZ, AMANDA; GUIJARRO, BEATRIZ; MASSUTÍ, ENRIC (Mediterranean Marine Science, 2025)
The bamboo coral Isidella elongata (Esper, 1788) is a near-endemic species of the Mediterranean Sea, which forms dense aggregations on bathyal muddy bottoms and contributes to the three-dimensional structure of bathyal environments. Isidella elongata populations have experienced a regression since the middle of the last century; it has been attributed to the impact of bottom trawling. In this work, we report the identification of I. elongata colonies, both dead and alive, during scientific surveys conducted in the western Mediterranean Sea. We also characterise the associated benthic and nekto-benthic assemblages and analyse the presence of the species relative to trawl fishing grounds. One field of I. elongata was identified off south-eastern Menorca, from photogrammetric sledge images. The presence of the species was also detected in beam trawl and experimental bottom trawl samples in the Ibiza Channel, and in several Remotely Operated Vehicle (ROV) and beam trawl sampling stations in Ses Olives seamount in the Mallorca Channel. The I. elongata field observed off south-eastern Menorca was one of the densest (with maximum values of 6.7 colonies/m2) described thus far in the western Mediterranean Sea. The identification and location of these habitats are of high conservation interest, as they can be useful for an appropriate spatial planning of marine areas and ecosystem-based fisheries management; this information could be especially relevant for an adequate management of deep-water benthic habitats and living resources. The challenge is to combine the conservation of ecosystems with the sustainability of fisheries, which are both objectives of the Common Fisheries Policy and the Marine Strategy Framework Directive.